Kesinambungan Dan Perubahan Spasial Pada Rumah Tradisional Buton Di Kawasan Benteng Kraton Buton Sulawesi Tenggara - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Butonese traditional house has a shape of grandstand house which its construction was inheritance to generation by generation has been experiencing some changes in their developments. The objectives in this study are to find the spatial continuity and change of Butonese traditional house and the influencing factors. This research is using rationality qualitative method. The review entity becoming an analysis unit is Butonese traditional house is located inside the palace fort. Samples were determined purposively. The data collecting was done by measurements, observations, interviews, photos and sketch drawing. Data analysis made inductively that is making an abstract and groupped based on units. Analysis is helped by category and description techniques. The results in this study are physical and nonphysical findings.The nonphysical finding is custom ceremonial tradition activities tend to continue